Auto-Mobile Language Learning: Autonomous Language Learning Based on the Practicality of Mobile Applications - Anis Firdatul Rochma; Sulis Triyono (International Journal of Pedagogy and Teacher Education, 2019)
Establishing autonomous language learning is believed to be critical because it contributes to learners’ capabilities in independently mastering a target language. One of many strategies employed to develop learner autonomy is to incorporate modern technology, such as smartphones, into language learning activities (Steel, 2012). However, the implementation of modern technology in the learning process seems quite ineffective in creating situations in which the learner’s autonomy is achieved (Na, 2018). Henceforth, the present study is projected to seek the beneficial impacts of the Edmodo, Duolingo, Memrise, Socrative and Quizlet applications. The qualitative method and the substitution-augmentation-modification-redefinition model are adopted to examine and discuss the findings. Employing mobile applications facilitates learners to not only learn the language but also to acquire the target language to develop their language competence. Additionally, incorporating mobile applications can assist learners in fostering self-instructed, self-directed, self-accessed learning, and the individualised instruction of language learners.